'The Most Serious Dissention': Implications of a Theological Reading of the Keithian Controversy. Issue 1 (1st June 2022) - Pennington, Madeleine
Abstract : The Keithian Controversy was one of the most explosive disputes in seventeenth-century Quakerism, but has been neglected in the historiography. Where it has attracted attention, it has usually been assumed that Keith himself was the problem, and the theological contours of the controversy have therefore been given little consideration. Nonetheless, the heart of the controversy was a critical spiritual issue for the Religious Society of Friends: what is the relationship between the Light within and the historical Jesus? This research note reflects on some of the implications of this view for our wider understanding of Quakerism. Above all, it suggests that the Keithian controversy points to intrinsic tensions within Quaker thought, and was the first in a series of Quaker schisms that confronted these issues explicitly. The benefits of studying the Controversy for a more contextualised understanding of all periods of Quakerism are therefore significant.